2003
DOI: 10.1164/rccm.200301-072oc
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation in Severe Hypoxemic Respiratory Failure

Abstract: The efficacy of noninvasive ventilation (NIV) to avoid intubation and improve survival was assessed in 105 patients with severe acute hypoxemic respiratory failure (arterial O2 tension or saturation persistently 60 mm Hg or less or 90% or less, respectively; breathing conventional Venturi oxygen at a maximal concentration [50%]), excluding hypercapnia, admitted into intensive care units of three hospitals. Patients were randomly allocated within 24 hours of fulfilling inclusion criteria to receive NIV (n=51) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
319
6
33

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 535 publications
(375 citation statements)
references
References 29 publications
17
319
6
33
Order By: Relevance
“…Moreover, Gray et al, [24] did not find the difference in intubation or mortality rates with either CPAP or Bi-PAP compared to oxygen therapy. In contrast, previous trials [21,25] found that Bi-PAP reduced the need for invasive mechanical ventilation, and endotracheal intubation when compared with oxygen therapy.…”
Section: Introductioncontrasting
confidence: 58%
“…Moreover, Gray et al, [24] did not find the difference in intubation or mortality rates with either CPAP or Bi-PAP compared to oxygen therapy. In contrast, previous trials [21,25] found that Bi-PAP reduced the need for invasive mechanical ventilation, and endotracheal intubation when compared with oxygen therapy.…”
Section: Introductioncontrasting
confidence: 58%
“…Finally, the number of included patients was small and as our group of patients included those admitted for acute respiratory failure and those at risk of developing respiratory failure after extubation, the group was heterogeneous. Nonetheless, despite this heterogeneity, all patients received NIV for well-validated indications [3,17,18]. It must also be pointed out that our study was a short-term evaluation and that the included patients were not in severe respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive care patients receiving NIV via an oronasal face mask for acute respiratory failure [17,18] or for being at risk of postextubation respiratory failure according to previously published criteria [3] were eligible for inclusion in the study. Exclusion criteria are outlined in the Electronic Supplementary Material.…”
Section: Patientsmentioning
confidence: 99%
“…Non-invasive ventilation has been demonstrated to be beneficial for the outcome of patients with acute exacerbation of chronic obstructive pulmonary disease, acute cardiogenic pulmonary oedema, and more recently in the weaning/post-extubation management oe ARF. Non-invasive ventilation can also prevent intubation in selected patients with severe hypoxemic or de novo ARF [3], particularly in the postoperative period [4]. However, its clinical benefit remains controversial for the management of hypoxemic patients [5].…”
mentioning
confidence: 99%
“…In fact, several factors (Table 1) may explain the discrepancy of NIV results in hypoxemic ARF, with a failure rate (intubation) ranging from 25 to 60% [3] and an intensive care unit (ICU) mortality rate after intubation reaching up to 60% [8]. Heterogeneity in the underlying aetiology and severity of ARF is probably one of the main confounding factors.…”
mentioning
confidence: 99%